Author Correction: Computer keyboard interaction as an indicator of early Parkinson's disease. Issue 1 (December 2018) - Giancardo, L.; Sánchez-Ferro, A.; Arroyo-Gallego, T.; Butterworth, I.; Mendoza, C.; Montero, P.; Matarazzo, M.; Obeso, J.; Gray, M.; Estépar, R.
A correction has been published and is appended to both the HTML and PDF versions of this paper. The error has not been fixed in the paper.